Bio-inspired trust management in distributed systems - A critical review - Firdhous, Mohamed; Hassan, Suhaidi; Ghazali, Osman; Mahmuddin, Massudi (2012)
Distributed computing has grown rapidly in the recent years.In addition to the increase in the size of individual networks, new types of networks have also emerged providing different types of services to clients. While these systems provide an invaluable service, they also face certain practical issues.Security is one of the most important issues, that must be dealt with by the implementers in order to provide a satisfactory service.Trust and trust management have been drawing the attention of security researchers in order to identify the malicious nodes and separate them from good benevolent nodes and also to quantify the quality of services provided by the nodes in a system.Several trust computing models have been proposed for distributed systems by various researchers.These models are based on different approaches from fuzzy logic, Bayesian model, social networking to bio-inspired mechanisms.In this paper, the authors take a critical look at the bio-inspired trust models reported in the literature with respect to their principles, advantages and disadvantages.